Economic relations of Africa with the socialist countries : proceedings of the 5th International Conference of the Socialist Countries' Africanists, November 1976, Budapest - Institute for World Economics, The Hungarian Academy of Sciences (Budapest : Institute for World Economics of the Hungarian Academy of Sciences distributed [by] StechertHafner, 1978)
This paper discusses the relations between the African countries and the socialist countries
Conference held under the auspices of the Institute for World Economics of the Hungarian Academy of Sciences.
Includes bibliographical references.
osc 06/03/2019
Loans
Keywords: Africa; Communist countries